Tear me apart - Ellison, J. T. (MIRA, 2018)
Competitive skier Mindy Wright is a superstar in the making until a spectacular downhill crash threatens not just her racing career but her life. During surgery, doctors discover she's suffering from a severe form of leukemia, and a stem cell transplant is her only hope. But when her parents are tested, a frightening truth emerges. Mindy is not their daughter. The race to save Mindy's life means unraveling years of lies. Was she accidentally switched at birth or is there something more sinister at play? The search for the truth will tear a family apart...and someone is going to deadly extremes to protect the family's deepest secrets.